2018
DOI: 10.1080/10803548.2018.1495899
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pattern and correlates of work-related musculoskeletal disorders among school teachers in Enugu, Nigeria

Abstract: There was a prevalence of work-related MSDs among the teachers. Advanced educational qualification, elevated teaching boards, teaching experience over 10 years and age range of 35-50 years were the major predictors of MSDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 35 publications
9
35
0
2
Order By: Relevance
“…This was higher than the rates reported by teachers in China with 48.7% in the neck and 45.6% in the neck/shoulders (23); Turkey with 43.8% in the lower back, 42.5% in the neck, and 43.8% in the shoulders (45); and Brazil with 49.6% in the lower back and 50.2% in the neck (19). These results place Chilean urban teachers among those with the highest MSD prevalence in these body segments, similar to teachers in Nigeria with 62.3% in the shoulders and 57.9% in the neck (12); Saudi Arabia with 63.8% in the lower back, 45.4% in the shoulders, and 42.1% in the neck (16); or Kenya with 64.98% in the lower back (21). It should be considered that in this study all urban teachers did classes in primary and/or secondary schools.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This was higher than the rates reported by teachers in China with 48.7% in the neck and 45.6% in the neck/shoulders (23); Turkey with 43.8% in the lower back, 42.5% in the neck, and 43.8% in the shoulders (45); and Brazil with 49.6% in the lower back and 50.2% in the neck (19). These results place Chilean urban teachers among those with the highest MSD prevalence in these body segments, similar to teachers in Nigeria with 62.3% in the shoulders and 57.9% in the neck (12); Saudi Arabia with 63.8% in the lower back, 45.4% in the shoulders, and 42.1% in the neck (16); or Kenya with 64.98% in the lower back (21). It should be considered that in this study all urban teachers did classes in primary and/or secondary schools.…”
Section: Discussionmentioning
confidence: 71%
“…One of the professions with the highest MSD rate worldwide is school teaching (9)(10)(11). Furthermore, a close relation exists between MSD and classroom experience years, age range, female gender (12), obesity (13)(14)(15), school type and number of students assigned (16), school infrastructure, work conditions, high stress, and psychosocial factors (4,10,(17)(18)(19), with links even being observed with the urban or rural area where teachers work (20). MSDs have been studied in both developed and developing countries, with high prevalence in body segments including the lower back, neck, shoulders, and upper limbs (14,(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, physical activity was also significantly associated with a lower prevalence of dorsal pain in secondary teachers in Botswana [ 10 ] and with any MSDs in female teachers in Saudi Arabia [ 1 ]. The possible reasons that can explain these results is that exercises can improve strength, flexibility, pain threshold and makes muscles and ligaments stronger for optimal functioning and prevents injury [ 17 ]. This is particularly useful for teachers who frequently use awkward and long-lasting standing positions.…”
Section: Discussionmentioning
confidence: 99%
“…Another South African study (Eggers, 2016) reported the prevalence of neck/shoulder injuries among school teachers at 83.1%. Similarly, studies in Hong Kong (Chong & Chan, 2010), Taiwan (Cheng, Wong, Yu, & Ju, 2016) and Nigeria (Ojukwu et al, 2018) reported shoulder injury as the most prevalent at 73.4%, 63.4% 62.3% respectively. On the other hand, a study in Egypt (El-Sayed Ebied, 2015) reported the lowest prevalence (15%) of shoulder injuries.…”
Section: Discussionmentioning
confidence: 77%